Wie Bewegungen Einfluss auf kognitive Entscheidungen nehmen - Green, N.; Raab, M. (Messplätze, Messplatztraining, motorisches Lernen: ausgewählte Beiträge; 5. gemeinsames Symposium der dvs-Sektionen Biomechanik, Sportmotorik und Trainingswissenschaft; Universität Leipzig, Sportwissenschaftliche Fakultät, 19. bis 21. September 2002 / Veranst.: Sportwissenschaftliche Fakultät der Universität Leipzig ..., 2003)
Do motion signals provide an effect on cognitive information processing? In our work we highlight a function-based approach towards the nonaffective tuning of arm movements on heuristic vs. systematic decision-making processing stages. Our first experimental study indicates that this approach serves as a plausible alternative to other cognitive-tuning models. 40 participants had to move toward an extension or flexion position with either a movement goal that connects the movement with an avoidance or an approach function. The results support that the approach function of the movement enhances heuristic processes in an as-sociation task, whereas the avoidance function of a movement enhances sys-tematic processes within the same arm position. Cognitive tuning models, which argue that the position of the movement tunes cognitive processes cannot explain this effect.